Hyperresponsiveness in the Human Nasal Airway: New Targets for the Treatment of Allergic Airway Disease - P. J. Turner; J. C. Foreman (Mediators of Inflammation)
Allergic rhinitis is a condition which affects over 15% of the population in the United Kingdom. The pathological process involves two stages: nasal inflammation, and the development of nasal airway hyperresponsiveness (AHR) to allergen and a number of other stimuli. This results in the amplification of any subsequent allergic reaction, contributing to the chronic allergic state. A number of different hypotheses have been proposed to explain the underlying mechanism of AHR, including a role for eosinophil-derived proteins, free radicals and neuropeptides. While there may be a number of independent pathways which can result in AHR, evidence obtained from both animal models and in vivo experiments in humans indicate that some mediators may interact with one another, resulting in AHR. Further research into these interactions may open new avenues for the pharmacological treatment of chronic allergic rhinitis, and possibly other allergic airway diseases.